English teachers' reflections of the integration of intercultural competence into their teaching practices: What and how? - Ahmad Sugianto (Universitas Musamus, 2021)
In this globalization era, the English teaching is expected to not only exhort language skills but also promote the effective communication involving cultures is crucial. This study aims to scrutinize the way the English teachers reflect the (inter)cultural competence incorporated into their English instructions. Thirty one English teachers studying at a university in Bandung were involved. The data were gleaned through questionnaires and interviews. Findings reveal that the teachers have various levels of beliefs in incorporating cultures and intercultural competence in English teaching practices. In this regard, 35.48% were found to be in the moderate level, 25.81% in the good level, 22.58% in the low level, and 16.13% were categorised into a high level. Moreover, in all aspects of the familiarity of the target cultures, most of the teachers were categorised to have a moderate level. Furthermore, storytelling constitutes the most frequently used technique by the teachers. Besides, the English teachers perceived that some challenges were still emerged during the practice of integration of target cultures into English teaching practices. Thus, some systematic endeavors to endorse it are advocated.